Effect of Hot Breaking and Cold Breaking on the Rheology of Tomato Paste (Lycopersicon Esculentum Mill) - Selpiah; Salengke; Iqbal (CV. Syntax Corporation Indonesia, 2025)
Tomato paste quality hinges on processing methods, with hot break (95°C) and cold break (65°C) treatments critically impacting rheology and shelf life. Prior studies lack comprehensive analysis of prolonged heating durations and storage effects on viscosity stability. This study examines how hot/cold break treatments influence tomato paste rheology, enzyme activity (PME, PG), and storage stability to identify optimal processing parameters. Tomatoes were heated at 65°C (cold break) or 95°C (hot break) for 5–15 minutes, processed into paste, and stored for 5 weeks. Rheological properties (flow index *n*, consistency coefficient *k*) were measured weekly using a viscometer (30–60°C), while PME/PG activities were assayed titrimetrically and via DNS. Hot break at 45°C with 10-minute heating yielded the highest viscosity stability (*n* = 0.3685, *k* = 1.478) and extended shelf life by reducing microbes. PG enzymes were more heat-resistant than PME, with cold break showing higher residual activity (27.72% PME, 35% PG after 5 weeks). Storage revealed pseudoplastic degradation, with 60°C treatments exhibiting drastic *k*-value declines ( 50%). The 10-minute hot break at 45°C is recommended for industrial tomato paste production to balance viscosity and shelf life. Future research should explore hybrid thermal treatments to enhance nutritional retention, building on findings by Wang et al. (2023).